CHEMICAL DEGRADATION OF NAFION MEMBRANES UNDER PEMFC AS INVESTIGATED BY DFT METHOD - Sanjaya, Rochmad K; Juliandri, Juliandri; Rahayu, Iman; Ismillayli, Nurul; hermanto, dhony (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2020)
CHEMICAL DEGRADATION OF NAFION MEMBRANES UNDER PEMFC AS INVESTIGATED BY DFT METHOD. An exsitu method has been developed to performance of Nafion's membrane in PEMFC (Proton Electrolyt Membrane Fuel Cells), caused by the chemical degradation of ·OH and ∙H radicals. The change of the chemical structure occurring during the degradation were primarily calculated of the relative energy of reactions by DFT (Density Functional Theory) method approach in the Gaussian software. This study aims to determine whether DFT method with functional B3LYP, PBEPBE, and B3PW91 and base sets 6-311++G can be used in determining the relative energy of a reaction and knowing the difference in role between ·OH and ∙H in the degradation process of the main chain Nafion with the final group are -CF2H, -CF=CF2 and -COOH. The three functionalities applied showed that the ·OH radical has more role than the ∙H radical in the degradation process of the Nafion main chain. In the -CF2H group was shown the relative energy value of reaction 2 is lower than reaction 5, in the -CF=CF2 group was shown the relative energy value of reaction 8* is lower than reaction 11 and in the -COOH group the relative energ value of reaction 14 is lower than reaction 16. By knowing the relative energy of the Nafion main chain degradation reaction with a certain final group and the role of certain radical compounds in the degradation process, the DFT method with functional B3LYP, PBEPBE and B3PW91 and base sets 6-311++G can recommend various modifications of the Nafion as a fuel cell membrane, particularly in increasing of membrane performance.